The Influence of Microbicidal Substances on the Properties of Cellulosic and Lignocellulosic Materials - Mikala, Ondřej; Gojný, Jan; Milichovský, Miloslav; Hájek, Matěj (Česká společnost průmyslové chemie, 2016)
An unsuitable storage of books can cause microbiological attack. The biological attack can be caused by bacteria or fungi. The next type of degradation reaction is hydrolysis, which is supported mainly by increased content of water in books. In this case is degraded the whole cellulose structure. This work is focused on the influence of three components of essential oils on strength and optical properties of lignocellulosic materials. These components, with their microbicidal effects and their hydrophobic character, could serve as protection of archive materials on cellulosic base. For testing were used cellulosic and lignocellulosic materials, common used in paper industry (coniferous sulphate pulp, deciduous sulphate pulp, sulphite pulp, groundwood, pulp for the production of handmade paper and sample of historical paper). It was proved no deteriorate effect of basic components composing of essential oils (EO) upon strength properties of paper matter.
Vliv mikrobicidních látek na vlastnosti celulózových a lignocelulózových materiálů
Keywords: lignocellulose materials; essential oils; optical properties; mechanical properties; lignocelulózový materiál; esenciální oleje; optické vlastnosti; mechanické vlastnosti